Expression analysis of diosgenin pathway genes and diosgenin accumulation in fenugreek sprouts after exposure to copper sulfate - Kwon, Do Yeon; Sathasivam, Ramaraj; Kim, Yeon Bok; Kim, Haeng-Hoon; Park, Sang Un; Park, Byung Bae (Journal of Phytology, 2022)
Trigonella foenum-graecum L. is an annual herb belonging to the family Fabaceae commonly called Fenugreek. It is rich in various secondary metabolites such as alkaloids, flavonoids, phenolic compounds, and steroidal saponins. In recent years, diosgenin has much attention in the cosmetic, functional food, and pharmaceutical industries. In this study we aimed to examine the effect of different concentrations of copper sulfate (CuSO4) on growth, diosgenin biosynthetic (DB) gene expression, and diosgenin accumulation in T. foenum-graecum sprouts. Results showed that the seed germination, fresh weight, shoot length, and root length were gradually decreased with increasing the CuSO4 concentrations. In contrast, the expression level of DBGs i.e., TfSQS, TfSQLE, TfCAS, and TfSTRL were gradually upregulated with increasing the CuSO4 concentrations. Among all those tested concentrations, the expression levels of all those genes were significantly higher in 0.5 mM CuSO4 treated sprouts. The highest expression level was obtained in the TfCAS gene, which was 3.25-fold higher than the unexposed sprouts. The diosgenin content was significantly influenced in the CuSO4 exposed sprouts. The highest diosgenin content was achieved in the 5.0 mM followed by 1.0, 10.0, and 0.5 mM CuSO4 exposed concentrations, with a reduction of 41%, 39%, 36%, and 35%, respectively. From these results, it is shown that exposure of fenugreek sprout to CuSO4 is one of the suitable strategies to enhance the accumulation of diosgenin content.